Bullying a guide to research, intervention, and prevention - Mishna, Faye. (New York ; Oxford : Oxford University Press, 2012)
This title provides an integrated, nuanced synthesis of current and cutting-edge scholarship on bullying that will appeal to students, practitioners, and researchers in social work education, and psychology.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Bullying; Bullying -- Prevention; Bullying in schools; Cyberbullying